Cayman Islands : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper focuses on observance of standards and codes on the Financial Action Task Force (FATF) recommendations for antimoney laundering and combating the financing of terrorism (AML/CFT) for the Cayman Islands. The assessment reveals that the Cayman Islands's legal framework for combating money laundering and terrorism financing is comprehensive. All designated categories of offences enumerated in the FATF 40 Recommendations are predicate offences under the Cayman law. The criminalization of FT is in accordance with FATF requirements. The confiscation regime meets most standards and is effective.